Ecological aspects of American cutaneous leishmaniasis: 4. Observations on the endophilic behavior of the sandfly and the vectorial role of Psychodopygus intermedius in the Ribeira Valley region of the S.Paulo State, Brazil Aspectos ecológicos da leishmaniose tegumentar americana: 4. Observações sobre o comportamento endófilo de flebotomíneos e papel vetorial de Psychodopygus intermedius na região do Vale do Ribeira, Estado de São Paulo, Brasil - Almério de Castro Gomes; Jair Lício Ferreira Santos; Eunice Aparecida Bianchi Galati (Universidade de São Paulo, 1986)
The invasive tendency of Psychodopygus intermedius in the home environment, observed initially by Forattini et al. (1976), has now been confirmed by the demonstration of its high endophilic ability and by the use of human residences for shelter. Populations such as Lutzomyia migonei and Pintomyia fischeri were also present in that environment, though their low densities registered during this investigation could be an indication of their poor ability to overcome the barriers raised by the artificial environment. An objective epidemiological analysis based on the variables here given showed that human infection takes place in the extraforest environment, and the principal vectorial function falls, without doubt, on P. intermedius. A tendência invasiva de Psychodopygus intermedius ao ambiente domiciliar, observada inicialmente por Forattini e col. (1976), foi agora confirmada através de comprovação da sua elevada capacidade endófila e uso da habitação humana como abrigo. Populações como Lutzomyia migonei e Pintomyia fischeri também estiveram presentes naquele ambiente, porém suas baixas densidades assinaladas nesta investigação poderão indicar pouca capacidade para vencerem as barreiras impostas pelo ambiente artificial. Uma análise epidemiológica objetiva, baseada nas variáveis incluídas, demonstrou que a infecção humana ocorre em ambiente extraflorestal, cuja função vetorial principal recaiu sobre P. intermedius.